Profile of milk consumers and determinants of A2A2 milk consumption in the Tocantins State - Rodolfo Olinto Rotoli Garcia Oliveira; Ana Beatriz Bezerra Souza; Raryanne Dias Folhas; Marcelo Corrêa da Silva; Itallo Romero Marques Sobreira; Mariane Santos Pereira; José Bento Sterman Ferraz; Minos Esperandio de Carvalho; Leandro Lopes Nepomuceno; Helcileia Dias Santos; José Américo Soares Garcia; Jorge Luís (Brazilian Journal of Veterinary Research and Animal Science, 2023)
The dairy industry diversifies products with organoleptic, dietary, functional, and nutritional properties according to consumer demands and welfare. This study aimed to examine the profile of consumers, data on milk consumption, knowledge, and familiarity with A2A2 milk in the Tocantins State, Brazil. A qualitative survey was carried out through a questionnaire applied to 389 people, distributed in 34 municipalities. Regarding the consumption of dairy products, 21.31% of participants described having some type of discomfort when consuming them. Among participants, 46.27% consumed one to two liters, 28.28% two to four liters, and 25.45% more than four liters per week. Milk was the main dairy product consumed, according to 59.13% of participants. Of all respondents, 76.10% pay little or no attention to the information on the label, versus 23.90% who did not. Regarding A2A2 milk, 40.36% possessed some knowledge about it, while 59.64% did not. 42.93% and 30.59% of participants stated they would be willing to pay over 10% or 50% more, respectively, whereas 24.94% would not pay any additional amount on the price of A2A2 milk. Willingness to pay a low additional amount was related to consumers who heard of, but knew little about this product, whereas the likelihood of paying higher additional amounts was associated with respondents who heard and know about the product.